Sonochemical Degradation of N-Methylpyrrolidone and Its Influence on Single Walled Carbon Nanotube Dispersion - Yau,H; Shaffer,MSP (Chemical Communications, 2015)
Sonicating pure N-methyl pyrrolidone (NMP) rapidly produces contaminating organic nanoparticles, at increasing concentration with time, as investigated by AFM, as well as UV-vis, IR and NMR spectroscopies. The contamination issue affects nanotube, and likely other nanomaterial, dispersions processed by sonication in organic solvents.